Rock mass characterization for shallow granite by integrating rock core indices and seismic velocity. (March 2017) - Lin, Daming; Lou, Feng; Yuan, Renmao; Shang, Yanjun; Zhao, Yun; MA, Jilei; Zhang, Lan; Li, Kun; Bao, Weixing
Abstract: Mechanical and geophysical properties obviously vary between rocks and rock masses. In general, rock mass structures are seldom analyzed quantitatively based on geophysical information. In this paper, the authors combine data from 278 shallow boreholes and 12 CSNS engineering geo-exploration lines in a granitic area in South China and use the GOCAD software platform to establish a three-dimensional geological-geophysical model. A quantitative relationship between the rock mass structure and granitic RCI (rock core index) is then established. An empirical relationship between the RCI and the seismic velocity of the rock mass is also obtained, which is helpful for analyzing the features of the rock mass. This research improves the quantitative study of rock mass structures using geophysical parameters, which is helpful for the prevention of geological disasters along the highway in the granitic area. Highlights: Relationship between the rock mass structure and granitic RCI is established. Relationship between the RCI and the seismic velocity of a rock mass is also obtained. Quantitative study of rock mass structures using geophysical parameters is improved.